ANALYSIS OF CHARACTER VALUES THROUGH ITP AND ATP TECHNOLOGY AS ONE OF THE INNOVATIONS IN LEARNING ELEMENTARY SCHOOL EDUCATION TO OVERCOME DEGRADATION - Cut Nurul Zara Vonna; Fenti Retnoningrum; Indah Novita Sari; Muhamad Chamdani (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
The development of time because of the existence of globalization led to moral degradation in children. To overcome the moral degradation of the child, it is necessary to have learning innovations in improving the quality of basic education which requires an analysis of character education using methods of observation and questionnaire by entering the results of analysis into ITP software (Development Task Inventory) and  ATP (Analysis of Development Task). The existence of ITP and ATP can identify the level of development of aspects related to character education in primary school. Based on preliminary observations, it was found that many teachers did not know the level of children's character development. The article aims to: (1) educators can identify the level of students character (2) educators can design good learning based on the results of each student's character analysis. The conclusion of this study is that educators can develop children's character levels.